2006
DOI: 10.1111/j.1399-3046.2006.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Organ transplantation, organ donation and mental retardation

Abstract: We reviewed the literature on accessibility and outcomes of organ transplantation in individuals with mental retardation (MR) and on the prevalence of organ donation in this population. Six centers have published outcome data on renal transplantation in 34 individuals with MR. The one- and three-yr patient survival rates were 100% and 90%, respectively. The studies reported good compliance with post-transplant medications due to consistent support from family members or caregivers. The outcome studies for live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…This survey suggests that most centers considered neurodevelopmental disability in a way that was unsystematic and potentially biased, lacked public transparency or input, and lacked justification through appeals to ethical standards. This finding is consistent with a 2004 survey of members of the ARC of the United States (an ID family organization) in which 80% of responders believed that people with ID are discriminated against with regard to access to organ transplant operations …”
Section: Provider Attitudes and Guidelinessupporting
confidence: 88%
“…This survey suggests that most centers considered neurodevelopmental disability in a way that was unsystematic and potentially biased, lacked public transparency or input, and lacked justification through appeals to ethical standards. This finding is consistent with a 2004 survey of members of the ARC of the United States (an ID family organization) in which 80% of responders believed that people with ID are discriminated against with regard to access to organ transplant operations …”
Section: Provider Attitudes and Guidelinessupporting
confidence: 88%
“…Despite these recommendations, a 2005 survey of pediatric transplant centers reported 56% of transplant centers would consider IQ <35 a relative contraindication to solid organ transplantation and 40% would consider it an absolute contraindication . Some centers would only consider a child with ID for organ transplant if a parent or family member agreed to be a living donor rather than to list the child for a deceased donor transplant .…”
mentioning
confidence: 99%
“…It is known that presence of a neurological condition is an exclusionary criterion to listing for some transplant programs. Richards et al found that 40% of US pediatric transplant programs would use severe or profound neurodevelopmental delay as an absolute contraindication to listing, even though those with neurodevelopmental delay have survival rates equivalent to others receiving transplant . The reasons for not listing a child with a currently manifesting neurological condition, let alone a child who has not yet developed an adult‐onset neurological condition are unknown, but raise questions about whether quality of life judgments may be at play, or if programs may be concerned that transplantation accelerates neurological disease.…”
Section: Discussionmentioning
confidence: 99%